Challenges and opportunities in promoting integrated coastal zone management in Algeria: Demonstration from the Algiers coast. (1st February 2019) - Khelil, Nawel; Larid, Mohamed; Grimes, Samir; Le Berre, Iwan; Peuziat, Ingrid
Abstract: Algeria as the Mediterranean countries is facing various challenges. Among them, the increasing of the population and their activities in the coastal zone, which impacts heavily the coastal and marine environment. Integrated Coastal Zone Management (ICZM) has been seen as an appropriate approach to tackle this situation. Algeria has set up numerous initiatives to strengthen its coastal governance, such as the Coastal Area Management Plan (CAMP) in the Algiers Coastal zone (ACZ) situated in the central part of Algeria. Also, various legal and institutional reinforcement have been done, like the enactment of a coastal law and the creation of agencies dedicated to coastal management. Even if assessment is seen as primordial in this process, yet few evaluations have been done in Algeria and particularly on the ACZ. This research paper aims is to assess the ICZM process in Algeria. A survey has been done with the various stakeholders involved in Coastal management at the different level of governance; national, regional and local in the ACZ. The objective was to assess the institutional capacities to implement the fundaments of ICZM. 7 parameters have been assessed: Data, interesectoriality, participation, legal framework, Capacity building, awareness and financial resources. A score for each parameter was set by the interviewees. Results shows that even some basements framework are now implemented, Algeria has still a long way to fully implement ICZM approach. Mainly regarding data management and the implementation of coastal monitoring systems, enhancing the coordination and participation of stakeholders, particularly the local communities and NGO's. The legal framework even it strengthening, a lot of efforts are still to be done for it real enforcement. The awareness and capacity building are still insufficient. Finally, sustainable funding for ICZM projects must be ensured. Highlights: The Algerian Coast is facing many environmental challenges. Integrated Coastal Zone management (ICZM) has been seen as an appropriate approach to tackle these challenges. ICZM process in the Algiers Coast has been assessed through the institutional capacities to implement ICZM principals. Even though considerable efforts have been made, Algeria has still a long way to go to implement fully ICZM approach. Focusing on Institutional capacities permits to highlight the critical aspect of governance to a better implementation ICZM process.